Epidemiologi Deskriptif Tuberkulosis di Kota Surabaya Tahun 2018-2022 - Asti Alya Rahmahdia; Siti Shofiya Novita Sari; Erni Astutik (Universitas Airlangga, 2024)
Background: Tuberculosis (TB) remains a top-ranking communicable disease in terms of morbidity and mortality factors in Indonesia. Surabaya city has the highest TB cases in East Java in 2022, with a prevalence rate of 355 per 100,000 population. Objectives: This study will provide an overview of tuberculosis cases in Surabaya City from 2018 to 2022. Methods: The research employs a descriptive approach using an ecological study design. The aggregate data sourced from the Surabaya City Health Office's reports, with the analysis unit being the sub-district, are utilized in this study. Other articles serve as comparative sources for the findings in this research. Results: Throughout the years 2018 to 2022, the spread of TB was higher in males than females, with a prevalence exceeding 53%. Based on regions, the prevalence of TB varies across different areas and does not always correlate with regions with high population and density. In terms of time, there was an increase in TB cases before and after the COVID-19 pandemic which is in 2021, there were 4,628 TB cases, which then rose to 8,218 cases in 2022. Conclusion: TB cases burden in Surabaya City among males during 2018-2022 surpassed females, attributed partly to lifestyle choices and smoking, while population density isn't always the primary factor in TB prevalence due to its multifactorial nature; moreover, the resurgence of TB cases post-pandemic doesn't necessarily signify negativity, as it might indicate improved TB case reporting compared to the COVID-19 pandemic period.